2D Seismic Data Analysis of Judaida Structure, Northern Iraq - Naji, Omar A.; AL-Kubaisi, Manal Sh.; AL-Heety, Emad A. (Iraqi Journal of Science, 2022)
This research aims to study the structural analysis of the 2D reflection seismic data for the Judaida subsurface structure located in Kirkuk province, northern Iraq. It is located 60 Km southwest of Kirkuk oil field, and 35 Km southwest of Jambur oil field, the Daquq River passes through the study area. The reflectors in the seismic section were picked and identified by using the synthetic seismograms generated from the logs data of the Jd-1 well. Three main seismic reflectors, Fatha, Jeribe, and the Euphrates were chosen. These mentioned sedimentary formations were deposited during the Middle Miocene, Lower Miocene, and Early-Mid Miocene respectively. Time and depth maps were drawn for these three reflectors by processing average data from Jd-1well. The structural interpretation results showed a structural closure on both time and depth domains in the middle of the study area. Judaida structure represented an asymmetrical longitudinal anticline fold. The Northeast limb has a dipping angle of 6-8 degrees more dip than the Southwest limb that has a dipping angle of 1-6 degrees, and the direction of the axis of the general structure is towards the Northwest-Southeast. The general dipping of the fold is toward the north east.